Opportunities to reuse fence posts using metal footings - Wong, Daniel (Acta silvae et ligni, 2025)
Residential wood fence posts may be dug directly into the ground, secured to a metal spike that goes into the ground, or secured to a concrete footing with a metal boot. It was hypothesized that, by keeping wood posts out of the ground, both spikes and boot attachments would increase protection against decay and termites and extend the service life of the posts. After 9 years of exposure in Kincardine, Ontario, Canada, at a site with decay and subterranean termites, we found that elevated fence post footings were associated with less biodegradation than posts dug directly into the soil. The spike and boot installations were particularly effective in reducing the incidence of termite attack under the conditions of this study. Spike and boot footings may offer a way to remediate posts by reusing the top portion of posts that were initially dug into the ground following a groundline failure.
Keywords: decay; fence posts; MCA; ograjni koli; ponovna uporaba; razkroj; rdeči bor; red pine; reuse; termites; termiti